2016
DOI: 10.1007/jhep01(2016)007
|View full text |Cite
|
Sign up to set email alerts
|

Warped flavor symmetry predictions for neutrino physics

Abstract: A realistic five-dimensional warped scenario with all standard model fields propagating in the bulk is proposed. Mass hierarchies would in principle be accounted for by judicious choices of the bulk mass parameters, while fermion mixing angles are restricted by a ∆(27) flavor symmetry broken on the branes by flavon fields.The latter gives stringent predictions for the neutrino mixing parameters, and the Dirac CP violation phase, all described in terms of only two independent parameters at leading order. The sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 88 publications
(130 reference statements)
2
72
2
1
Order By: Relevance
“…This constitutes a generalization of the idea of Randall and Sundrum whose aim was to address just the weak gauge hierarchy problem [5]. It has been shown that such a geometrical view of fermion mass hierarchies can be made consistent with the imposition of family symmetries to account for fermion mixing [6].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This constitutes a generalization of the idea of Randall and Sundrum whose aim was to address just the weak gauge hierarchy problem [5]. It has been shown that such a geometrical view of fermion mass hierarchies can be made consistent with the imposition of family symmetries to account for fermion mixing [6].…”
Section: Introductionmentioning
confidence: 93%
“…In order to simplify the analysis it is convenient to rescale the original radii of the torus as 2πR 1 ⇒ 1 and 2πR 2 ⇒ 1 and to adopt the complex notation z = x 5 + ix 6 With the help of the root of unity ω = e iθ = e 2iπ/3 , the symmetries of the orbifold from Eqs. (1,2) can be written as…”
Section: Theoretical Setupmentioning
confidence: 99%
“…As an example, in Fig. 3 we plot the allowed parameter space o two discrete symmetry based models, the Warped Flavour symmetry (WFS) model [41] -Left and the Revamped A 4 Babu-Ma-Valle (BMV) model [89] -Right. The black curves represents currently unconstrained (Standard-3ν) 90% C. L. regions for the neutrino parameters and the black point the best-fit value, while the blue region represents the 3σ allowed parameter space of the two models.…”
Section: Measurement Of Oscillation Parameters In Long-baseline Ementioning
confidence: 99%
“…It was used as a flavor symmetry for the first time by [84] and continues to be explored since θ 13 was measured [85][86][87][88][89][90][91][92][93][94][95][96][97][98]. A scenario that remains relatively unexplored is of combining discrete flavor symmetries with extra dimensions [57,80,[99][100][101][102][103][104]. In this work we consider using S 3 in a modified Randall-Sundrum 1 (RS1) [105] model, where the Higgs doublet is in the bulk.…”
Section: Introductionmentioning
confidence: 99%